Intestine-On-Chip: Enhancing In Vitro Intestinal Models Using Caco-2 and HT29-MTX Cocultures Under Different Flow Conditions - López, Rut; Bayona, Clara; Ochoa, Ignacio; Solanas, Estela (Jornada de Jóvenes Investigadores del I3A, 2024)
This study explores the development of in vitro intestinal models on chip using cocultures of Caco-2 and HT29-MTX cells over time under different flow conditions. For this purpose, cocultures in the chip were connected to a syringe pump with a characteristic shear stress of the intestinal epithelium, 0.02dyn/cm2 for 4 days and, compared to cocultures with non-specific flow by rocker for 21 days. The effect of different flow conditions in the intestinal permeability was assessed following the Lucifer Yellow assay. Coculture under specific flow conditions showed similar permeability values after 4 days to those under non-specific flow conditions after 14 days. Therefore, optimalization and further characterization of this model, may lead to a promising alternative for intestinal in vitro studies.